THE INFLUENCE OF DIGITAL PAYMENT, AND CUSTOMER EXPERIENCE ON PURCHASE DECISIONS MEDIATED BY IMPULSE PURCHASE BEHAVIOR IN FEB STUDENTS - Alifka Alya Zhafirah; Romansyah Sahabuddin; Tuti Supatminingsih (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of digital payment and customer experience on purchasing decisions, with impulsive buying behavior as a mediating variable among students at the Faculty of Economics and Business, Makassar State University. This study used a quantitative approach with a survey method. Data were collected through questionnaires. The data analysis method used was SEM (Structural Equation Modeling) using the Partial Least Squares (PLS) approach. The results showed that digital payment and customer experience significantly influenced impulsive buying behavior and purchase decisions. Furthermore, impulsive buying behavior also significantly influenced purchase decisions. The results of the mediation test demonstrated that impulsive buying behavior mediated the relationship between digital payment and purchase decisions, as well as between customer experience and purchase decisions. These findings suggest that the convenience of digital payment systems and a positive shopping experience can encourage impulsive purchases, ultimately strengthening students' purchase decisions.